Para além do “Eva viu a uva”: o colher e o semear sobre o caráter político-pedagógico e o trabalho socioeducativo de assistentes sociais - Silva, Williana Angelo da (2024)
The thesis integrates and deepens the analysis of the political-pedagogical character and socioeducational work of social workers, considering its materialization within the academic community, through the tension between different education projects based on the experience of members of the IFSP Social Workers Collective. In this sense, it was necessary to identify the implications, conflicts and influences of the contradictory conceptions and projects of education that have repercussions on the working conditions of social workers and their interrelationship with the other historical subjects involved in the educational process.As well as contributing to the systematization and analysis of the work of social workers from the IFSP Social Work Collective, focusing on the particularities of the political-pedagogical character and socio-educational work. In addition to identifying the dialectical relationship between social workers and the academic community in the exercise of the educational dimension inherent to the profession; and finally, to contribute to the analysis of the potential of socioeducational work in education policy, based on the axes of action and the horizon of emancipatory activities, as well as the challenges to its realization. In other words, the work sets itself the challenge of understanding what the political-pedagogical aspect of the profession is, what educational practice is ingrained in us and what we are actually daring to innovate in socio-educational work on the part of the reference professionals who make up the aforementioned Collective.The course of the qualitative research was developed based on the process of systematizing experiences, associated with the use of the memoir as a methodological resource with the reference social workers. We also counted on the participation of graduating students to contribute, from the memorial of their life and academic experiences, not strictly related to the interaction with the social workers; but rather relying on important aspects of the memories elaborated to build or legitimize part of the characterization of this complex field of work, which is professional and technological education; a space that reproduces values, cultures, conflicts, expressions of the social question.We can see that the objective conditions experienced have marked the materiality of the work and affected the meaning and/or the conditions for the realization of the professional project, at the same time as we suffer the constraints and illnesses of our salaried condition, intensified by the managerialist and bureaucratic processes in the work process. However, the Collective has the potential to generate acceptance for the professionals and to catalyze the forces in the processes of resistance, in the exercise of the political-pedagogical character and in the materialization of socio-educational work, marked by viable innovations in emancipatory and counter-hegemonic educational activities